PENINGKATAN PENGUASAAN KOSAKATA BAHASA ARAB MELALUI MEDIA FLASHCARD DAN PERMAINAN BENAR SALAH PADA SISWA KELAS I SD - Milati, Hana Indah; Addurrunnafisa, Balqis (Pengelola Jurnal Politeknik Negeri Ketapang, 2025)
Arabic language learning at the elementary school level plays an important role; however, it still faces challenges related to students’ low vocabulary mastery and learning enthusiasm due to the use of conventional teaching methods. This study aimed to improve students’ Arabic vocabulary mastery through the implementation of flashcard media and a true-false game for first-grade elementary school students. This research employed Classroom Action Research (CAR) conducted in two cycles consisting of planning, action, observation, and reflection stages. The research subjects were first-grade students, and the data were collected through oral tests, classroom observations, documentation, and teacher reflection notes. The results showed that the use of flashcards and the true-false game effectively improved students’ Arabic vocabulary mastery as well as their learning participation and enthusiasm. Improvements were indicated by more active student engagement, faster responses, and a more enjoyable and supportive classroom atmosphere in the following cycle. Therefore, flashcards and true-false games are effective learning strategies for enhancing Arabic vocabulary mastery among elementary school students.